"Les musées béninois: du musée ethnographique au musée d’histoire sociale’’ - EFFIBOLEY, EMERY PATRIC TODÉGNON ADÉBOLA (My University, 2015)
This paper is a review of the history of museums in the Republic of Benin which sheds light mainly on the specific history from 1920 to 1947. Museums in the country remain static in regards to their collections management and exhibitions though the government has been developing new projects. Privately-owned museums appearing since 1990s reflect the need for a paradigm shift, from the ethnographic museum to the cultural museum. This development requires the attention of policy-makers in order to address both social development and contemporary artistic creation.
Keywords: Dahomey-Bénin; musées; collections; politique culturelle; histoire des musées